IL-1 Receptor Regulates microRNA-135b Expression in a Negative Feedback Mechanism during Cigarette Smoke–Induced Inflammation - Halappanavar, Sabina (AAI, 2013)
Although microRNA-135b (miR-135b) is known to be associated with cancer, with recent work showing that it is massively induced in the pulmonary tissues of mice challenged with nanoparticles suggests a critical role for this microRNA in mediating inflammatory response. In this study, we investigated the expression and function of miR-135b in mice exposed to cigarette smoke or nontypeable Haemophilus influenzae (NTHi). Exposure to both cigarette smoke and NTHi elicited robust lung inflammation, but increased miR-135b expression was observed only in the lungs of cigarette smoke–exposed mice. Using IL-1R 1 knockout mice, we show that miR-135b expression is IL-1R1 dependent. A series of in vitro experiments confirmed the role of IL-1R1 in regulating miR-135b expression. In vitro activation of the IL-1R1 pathway in mouse embryonic fibroblast (NIH3T3) and lung epithelial (FE1) cells resulted in increased miR-135b, which was blocked by IL-1R1 antagonists or small interfering RNA–mediated silencing of IL-1R1 expression. Overexpression of mature miR-135b in NIH3T3 cells (pEGP-mmu-mir-135b) resulted in the suppression of endogenous levels of IL-1R1 expression. pEGP-mmu-miR-135b cells transiently transfected with luciferase reporter vector containing the 3′UTR of mouse IL-1R1 showed reduced luciferase activity. Finally, we demonstrate that miR-135b targets IL-1–stimulated activation of Caspase-1, the IL-1R1 downstream activator of IL-1β leading to suppressed synthesis of the active form of IL-1β protein. These results suggest that miR-135b expression during cigarette smoke–induced inflammation is regulated by IL-1R1 in a regulatory feedback mechanism to resolve inflammation.